2018
DOI: 10.1111/ane.13006
|View full text |Cite
|
Sign up to set email alerts
|

Electroclinical features of epilepsy monosomy 1p36 syndrome and their implications

Abstract: This syndrome represents a significant cause of IS: these patients, who develop IS, can suffer from pharmacoresistent epilepsy, that is more frequent in children with brain abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…On the functional level, OSAS in childhood may impair several neurocognitive functions such as executive functions, memory, motor control, attention, and visual-spatial skills [10, 11]. In addition, OSAS may be associated to emotional and mood dimensions [1215], autism spectrum disorders [16], primary headaches [17, 18], and epilepsy [1922].…”
Section: Introductionmentioning
confidence: 99%
“…On the functional level, OSAS in childhood may impair several neurocognitive functions such as executive functions, memory, motor control, attention, and visual-spatial skills [10, 11]. In addition, OSAS may be associated to emotional and mood dimensions [1215], autism spectrum disorders [16], primary headaches [17, 18], and epilepsy [1922].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been recently suggested that the leading type of seizures in these disorders is infantile spasm (36.4% of examined patients), which is not very common in our group of patients with GPIBD. This observation prompts the conclusion that the children presenting with dysmorphic features, neurodevelopmental delay, and early onset of epileptic seizures should be screened for both 1p36MS and GPIBDs, with infantile spams type of seizures being an important factor indicating the more probable diagnosis of 1p36MS ( 85 ). Our systematic review may serve as a basis for the comparison with both of these syndromes.…”
Section: Discussionmentioning
confidence: 80%
“…Diferrent critical region for epilepsy were delineated [ 92 , 93 , 94 ]. Haploinsufficiency of several genes was considered a potential contributor to seizures , such as GABRD ( delta subunit of the gamma-amino butyric acid receptor gene) , KCNAB2 (voltage-gated potassium channel subunit beta-2) gene and SKI (SKI proto-oncogene) [ 89 , 95 ].…”
Section: Monosomy 1p36mentioning
confidence: 99%
“…Various AEDs are reported in the literature for epilepsy treatment in 1p36 monosomy syndrome: high doses of oral steroids, VPA, LEV, VBG, ESM, PHB, association of VPA with ACTH or multidrug combination. The prognosis of epilepsy is reported as usually favourable; however a percentage of patients experience drug resistant seizures [ 85 , 89 , 90 , 95 ]. The onset of epilepsy with ISs, in 1p36 deletion syndrome, seems to be associated with a higher risk of developing refractory epilepsia [ 89 , 91 , 95 ].…”
Section: Monosomy 1p36mentioning
confidence: 99%